Study of acute toxicity, endothelial- and cardioprotective properties of phenolic and thiophenolic derivatives of 2H-imidazoles - O. A. Puchenkova; O. V. Shheblykina; D. A. Kostina; A. A. Bolgov; P. R. Lebedev; V. V. Molchanov; T. G. Pokrovskaya; M. V. Korokin; E. A. Nikiforov; N. F. Vaskina; T. A. Idrisov; T. D. Moseev; et al. (Фармация и фармакология (Пятигорск))
The aim. To study the acute toxicity, endothelial- and cardioprotective properties of phenolic and thiophenolic derivatives of 2H-imidazoles.Materials and methods. The study was performed on white laboratory female BALB/c mice (n=57) and male C57Bl/6 mice (n=66). Acute toxicity was assessed according to the interstate standard GOST 32644-2014 with histological evaluation of internal organs. Endothelial dysfunction was modeled by 7-day intraperitoneal administration of N-nitro-L-arginine methyl ester (L-NAME). The studied small molecules were administered intragastrically using a probe. To assess the endothelial protective effect, the levels of systolic and diastolic blood pressure were evaluated, as well as the coefficient of endothelial dysfunction; for the cardioprotective effect, the results of stress tests on the myocardium were evaluated.Results. The study of acute toxicity of the studied small molecules allowed us to classify them as class 4 and 5. The administration of compounds 1(a–d) and 2(a–c) to mice at a dose equal to 1/10 of LD50 led to changes in blood pressure and restoration of the dynamics of pharmacological tests in response to the administration of acetylcholine and sodium nitroprusside. Molecules 1b and 2c showed statistically significant endothelial protective activity in 3 doses (1/10, 1/50 and 1/100 of LD50). Also, these hit compounds demonstrated cardioprotective effects, recorded by the restoration of the functional capabilities of the myocardium in response to load and in the adrenoreactivity test, and to a lesser extent, during resistance exercise.Conclusion. The studied compounds have low toxicity and have endothelial- and cardioprotective effects. This study may contribute to the formation of an idea about further directions in the study of the pharmacological activity of these molecules from the group of phenolic and thiophenolic derivatives of 2H-imidazoles.